Strategic management of the Directorate General of Taxes to strengthen the state's financial stability - Aribowo, Irwan; Kumar, Jai; Kamilah, Niswatun Nurul (Educoretax, 2025)
The country's financial stability is a fundamental aspect that underlies the sustainability and economic development of a country. One of the most influential factors in maintaining this stability is state revenue, especially from the tax sector. In this context, the Directorate General of Taxes (DGT) plays a very strategic role in managing an efficient and effective tax system. The DGT is responsible for formulating and implementing policies that can optimize tax revenues to support the country's financial stability. This study aims to evaluate how strategic management is implemented by the DGT in order to achieve these goals. The main focus of this research is to identify the challenges and opportunities faced by the DGT in strengthening the country's financial stability through tax system reform. To achieve this goal, this study uses the strategic management theory of R. David, which includes three main aspects: strategy formulation, strategy implementation, and strategy evaluation. By analyzing each of these stages, this study seeks to provide insight into how the DGT can be more effective in carrying out its role and overcome existing obstacles in achieving the country's financial stability goals.